RESEARCHING STUDENTS’ INTERACTION IN COLLABORATIVE LEARNING CLASS - Lina Tri Astuty Beru Sembiring (Universitas Galuh, 2018)
Interaction as a part of students’ collaboration is an important aspect that needs to be considered in the teaching and learning process. An active interaction among students stimulates collaboration in their prior knowledge, perspectives and background experiences which later promote their high- level learning. It also affects the development of students’ learning process in the classroom. Nowadays, studies on interaction elaborate and become something challenging. Many theories have been developed by researchers, and each has its own strengths and weaknesses based on its needs and goals. In this study, the writer presents a library study of the types of students’ interaction and also a theory on researching students’ interaction developed by Kumpulainen and Wray. They have proposed three analytical dimensions of interaction namely: 1. the functions of verbal interaction which focuses on students’ verbal language, the character, and purpose of students utterances in peer group interaction, 2. cognitive processing that examined the ways in which students approached and processed learning tasks in their social interaction,3. social processing which examines the nature of the social relationships that were developed during students’ social activity. These elements are related and connected each other. However, a different kind of analysis is needed in order to analyze the elements through their analytic purposes. Keywords: Students’ interaction, researching students’ interaction, Collaborative learning class.